(untitled) (Mustansiria Dental Journal, 2018)
Background: The aim of study was to find out the prevalence of oral mucosal lesions in patients who are attending the oral diagnosis department of the College of Dentistry – Basrah University and compare it with the prevalence rates of these lesions in other parts of Iraq. Materials and Method: Oral examination of 2318 outpatients, 1202 females (51.8%) and 1116 males (48.2%). The patient’s age ranged between 9-74 years. All the patients of this study referred to oral diagnosis department, College of Dentistry, Basrah University seeking for dental treatment (from October 2010-May 2011). Results: Among the 2318 patients, only 206 patients (8.8%) had oral lesions. 115 males had oral lesion constituted 4.9% of total examined patients, while 91 females had oral lesion constituted 3.9%. The age range of the patients was between 9-74 years. Oral lesions were more prevalent among males (4.9%) than females (3.9%), and there was significant statistical difference between males and females. Oral lesions were classified according to the following 4 categories: ulcerated lesions (3.84%), benign lesions (2.93%) ,white lesions (1.12%) and candidiasis (0.99%), The most common oral lesion of the studied populations were the ulcerated lesions, which diagnosed in (3.8%).There were a significant statistical difference between males and females in the traumatic ulcer, lichen planus, pyogenic granuloma and peripheral giant cell granuloma. Conclusions: This study has provided information about the epidemiologic aspects of oral mucosal lesions that may prove valuable in planning of future oral health studies.